Age-Related Decrease in Striatal DA Produces Cognitive Deficits in Male Rats - Haider, Saida; Tabassum, Saiqa; Perveen, Tahira; Ali, Sarmad; Saleem, Sadia; Khan, Aisha Karim; Haleem, Darakhshan J. (Journal of Pharmacy and Nutrition Sciences, 2022)
Aging is a process that presents various alterations in physiological, behavioral and neurochemical processes. It causes impairment of CNS functions which lead to changes in memory, cognition and other behavioral performances. Reports have shown that aging causes neurochemical alterations in various physiological functions. The aim of the present study was to evaluate the cognitive changes in relation to process of aging. For this 20 male rats were taken, 10 young (4-6 months) and 10 old (18-22 months). Morris Water Maze (MWM) test was performed to monitor changes in learning and memory while Object-Recognition Task (ORT) was performed to evaluate changes in cognitive function. After behavioral assessment decapitation was done and rat brain was dissected to isolate striatum. Then neurochemical analysis was performed by HPLC-EC to monitor changes in striatal DA and DOPAC levels. Results of behavioral tests showed that aged rats exhibited a significant impairment of long-term memory. While cognitive ability assessed by ORT was also impaired in aged rats. Neurochemical results showed that there was a significant decline in striatal dopamine (DA) concentration while its metabolite DOPAC was significantly increased in aged rats. Hence aging has a significant negative influence on cognitive functions. Age-related behavioral deficits may occur as a result of decline in DA levels in striatum leading to changes in memory and cognitive performance.